THE CRISIS OF EFFICIENCY IN RESOURCE ALLOCATION IN ROMANIAS AGRICULTURE - Davidovici, Sava Alexandru (Economics of Agriculture, 2012)
The present paper highlights the peripheral position of Romanian farmers position in the European context. It reveals the causes of efficiency crisis that derives from the ownership structures, competition environment situation, the deficiencies of the institutional environment and the inconsistencies of the agricultural policies.